2009
DOI: 10.1080/17487870903314633
|View full text |Cite
|
Sign up to set email alerts
|

Economics and politics in the United States: a state‐level investigation

Abstract: We examine state income and government spending data to investigate the role of political parties and elections in state business cycles of the United States, and find strong support for the partisan political business cycles, both traditional and rational versions. The growth rate of per capita real income and government spending tend to be higher (lower) with a Democratic (Republican) governor as well as a Democratic (Republican) president. In case of economic growth, we find some evidence for opportunistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The finding that higher per capita income is associated with fiscal investments in EBT but that state budget strength was inversely related to such investments may seem counterintuitive on the surface; however, economic policy research has generally found that state-level infrastructure spending (which could extend to EBT implementation infrastructure) (1) tends to be unrelated to state per capita income [4244]; (2) is more common among Democratically controlled states (also related to EBT investment) [44, 45]; and, not surprisingly, (3) is associated with higher per capita state debt [46]. Although discussion of these dynamics is beyond the scope of this paper, such findings about the influence of “unmodifiable state factors” on EBT implementation investment provide a starting point for discussion.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that higher per capita income is associated with fiscal investments in EBT but that state budget strength was inversely related to such investments may seem counterintuitive on the surface; however, economic policy research has generally found that state-level infrastructure spending (which could extend to EBT implementation infrastructure) (1) tends to be unrelated to state per capita income [4244]; (2) is more common among Democratically controlled states (also related to EBT investment) [44, 45]; and, not surprisingly, (3) is associated with higher per capita state debt [46]. Although discussion of these dynamics is beyond the scope of this paper, such findings about the influence of “unmodifiable state factors” on EBT implementation investment provide a starting point for discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic controls differ across the two studies, including our use of a variable that measures the presence of a higher education campus. Of special note, Frank, Hoopes, and Lester (2020) include only a measure of lower state house partisanship, along with especially empirical papers on the role of economic and political variables in state government policy decisions, including Alt, Lessen, and Skilling (2002), Chang, Kim, and Ying (2009) variables that attempt to capture the process by which QOZ designation occurs; we include a similar measure of lower house partisanship along with additional measures of upper house partisanship and of legislature-governor partisanship. Even so, our estimation results are broadly similar to those of Frank, Hoopes, and Lester (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Confirming traditional partisan theory, many studies at the state level also find that leftwing politicians pursued more expansionary fiscal policy than rightwing politicians. 2 For example, Chang et al (2009) suggest that the growth rate of government spending was higher under Democratic governors. Besley and Case (1995) find that taxes and government spending was higher under Democratic governors even if the incumbent Democrat was ineligible for reelection because of term limits.…”
Section: Policies and Institutionsmentioning
confidence: 99%
“…Several studies have shown that party ideology influences economic policy-making in the United States. At the federal level and across the US states leftwing / Democrat governments seem to have pursued more expansionary fiscal policies than rightwing / Republican governments by increasing public expenditures and tax burdens (e.g., Alt and Lowry 1994;Blomberg and Hess 2003;Reed 2006;Rose 2006;Chang et al 2009;Broz 2011;Pickering and Rockey 2013). The result of ideology-induced fiscal policies across the US states is not only meaningful because states have the power to choose different policies and institutions.…”
Section: Introductionmentioning
confidence: 99%